The Role of Tennis in Promoting Students’ Physical Health and Psychological Development - Gengguo Tang (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The construction of campus tennis culture can cultivate lifelong sports awareness among college students, promote their comprehensive physical and mental development. The author conducted a survey on the current construction status of campus tennis culture in eight universities in Beijing from spiritual, material, behavioral, and institutional levels through methods such as questionnaire survey and interview. 165 college students, accounting for 33% of the total number, are very certain that tennis is a part of lifelong sports, and 102 college students, accounting for 20 4%, 91 college students with a general attitude, accounting for 18.2% of the total number, there is also a portion of college students who hold an attitude of uncertainty or below, accounting for 28.4%. The connotation of campus tennis spiritual culture is mainly summarized into three levels: core values, civilized moral etiquette, and psychological quality. Each level is based on the frequency of interviews and integrated to extract the core values of tennis sports spiritual culture, which are independence, perseverance, hard work, unity, and dedication; The civilized moral etiquette conveyed by tennis includes elegance, integrity, respect, fairness, and humility; The psychological qualities reflected in tennis are confidence, focus, positivity, optimism, and willpower.